Determination of paracetamol and caffeine in dosage forms by high performance liquid chromatography with photo diode array detection - Ismail, Ismazarni (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
A simple, accurate, and reproducible high performance liquid chromatographic method for the separation and simultaneous determination of paracetamol and caffeine in dosage forms is described. The HPLC system consisted of Water Alliance Series 2475 with photo diode array detection. The separations were c.arried out at room temperature on a C-8 (5 J.lffi, 250 x 4.6 mm i.d) Luna 5~ C-8 (2) Phenomenax Prodigy} analytical column. A mixture of 0.01 M KH2P04, methanol, acetonitrile, and isopropyl alcohol was used as mobile phase at a flow rate of 0.5 mllmin. Mobile phase solvents were degassed for 30 min. using ultrasonic bath and filtered through a 0.45 J.lm Milipore filter. The wavelength was in range of 210 to 400 nm. The validation validation linearity (r = 0.9998, 0.996 respectively for caffeine and paracetamol). The calculations of the concentration of paracetamol and caffeine were based on peak areas using calibration plots. The retention time of the separation of the mixture of caffeine and paracetamol were recorded as 11.695 min and 9.684 min respectively. This method is successfully applied to the analysis of commercial pharmaceutical preparations, yielding better resolution, sensitivity, and ease of operation as compared to the existing methods.